A Unified Spatial–Healing Threshold Model Explaining Minor Recurrent Aphthous Stomatitis - Yash Singh,; Dr SUMIT SINGH PHUKELA,; Parth Vikas Rao,; Rakshat,; Alan Aby, (The Bioscan, 2026)
Minor recurrent aphthous stomatitis (RAS) is a common, painful, and self-limiting disorder of the oral mucosa characterized by episodic ulceration, a strong predilection for non-keratinized sites, spontaneous healing, and migratory recurrence. Despite extensive investigation, prevailing trauma-based, immune-centric, and nutritional models fail to account simultaneously for the sharply localized onset of lesions, their intermittent nature, and their tendency to shift between sites. Here, we propose a Unified Spatial–Healing Threshold Model in which ulceration arises only when two necessary conditions converge at the same site and time: (i) the dynamic formation of localized epithelial–immune weak points driven by cumulative subclinical mechanical microstrain, and (ii) a transient reduction in epithelial reparative capacity due to systemic modifiers such as psychological stress or functional hematinic insufficiency. Ulceration represents a nonlinear threshold phenomenon. It occurs when the rate of epithelial damage exceeds contemporaneous repair capacity. Subsequent epithelial renewal restores local resistance, while redistribution of mechanical forces generates new vulnerable sites, explaining spontaneous healing and site-shifting recurrence. This unified framework integrates mechanobiological, immunological, and healing-based theories into a single coherent and testable model with clear clinical and research implications.